Transformasi Mindset Kerja Individu di PT. SPEM untuk Optimalisasi Kotribusi PAD Kota Pekanbaru - Leonardus Teguh Handoyo; Mhd Suleman Hsb; Dessy Andriani; Ferisca Nurwidyanti; Suryatunnisak Suryatunnisak; Dedi Kurnia; Zulfitri Zulfitri; Mukson Mukson; Lingga Ramadhana Arfi; Wandi Nur Ikhsan; Legia Seki Yolanda; Panzi Barza; Aswanto Aswanto; Deswita Deswita (Universitas Pahlawan Tuanku Tambusai, 2026)
One way to effectively contribute to regional revenue in Pekanbaru City is for PT. Sarana Pembangunan Energi Madani to transform the mindset of all employees. The purpose of this activity is to explore and explain the important role of mindset transformation in optimizing the contribution of regional original revenue. The method in this community service activity is service-learning based, by integrating academic learning with real services to PT. Sarana Pembangunan Energi Madani employees. The results of this activity are that mindset transformation is necessary for the company to be able to contribute to regional original revenue. The activity carried out with a soft skills-based approach and material presentation has a significant impact on employee mindset transformation.